RESPON KANDUNGAN LOGAM BERAT DAN PERTUMBUHAN TANAMAN SAWI (Brassica juncea) TERHADAP KOMBINASI MEDIA TANAM LUMPUR LAPINDO DAN MIKORIZA - Jeka Widiatmanta; Dita Serdani, Army (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2019)
This research is the development of the use of Lapindo mud and mycorrhizae as a planting medium. Lapindo mud contains nutrients such as N, P, K, Na, Ca, Mg, C organic and has a high cation exchange capacity. Mycorrhizae can increase the length of plant roots and are resistant to stress and soils contaminated with heavy metals. The study was arranged using a Randomized Block Design with factorial patterns, the first factor being the planting medium (A) and the second factor was mycorrhizae (P). The first factor is Lapindo mud and cow manure; Lapindo mud and goat manure; Lapindo mud and chicken manure with a ratio of 50%: 50%, respectively. From these two factors, 9 treatment combinations were obtained, namely A1P1, A1P2, A1P3, A2P1, A2P2, A2P3, A3P1, A3P2, and A3P3. Each treatment was repeated 3 times to obtain 27 experimental units. From the study found that there is a real interaction in providing a combination of planting media and mycorrhizae on the growth and yield of mustard plants. The best treatment combination was shown in the combination treatment of planting media (Lapindo mud and cow manure) with 10 gr mycorrhizae / plants (A1P2) on all observations (plant height, number of leaves, leaf area, fresh and dry weight of plants, root length, weight, weight wet and dry weight of root of mustard plants and absorption of heavy metal content).